The safety of neoadjuvant hormonal treatment in infants with cryptorchidism. Issue 6 (December 2022) - Fiala, Vojtech; Jiraskova, Zuzana; Drlik, Marcel; Sedlacek, Josef; Dite, Zdenek; Novakova, Petra; Kocvara, Radim; Kalousova, Marta; Soukup, Viktor
Summary: Background/Purpose: The standard treatment for boys with non-syndromic cryptorchidism is an early orchidopexy. It is unclear if surgical intervention alone is enough for future fertility. Recent studies show benefit of neoadjuvant or adjuvant hormonal treatment with gonadorelin (GnRH) for spermatogonia maturation based on testicular biopsy. The aim of this prospective study was to assess the safety of this treatment in infants with undescended testis at the recommended timing of early gonadorelin administration and timing of orchidopexy. Methods: Unilateral cryptorchid full term boys were initially examined (including hormonal, physical and ultrasound examination) at the age of 2.5–3.5 months. At 6 months of age, cryptorchidism was confirmed. Those with non-syndromic cryptorchidism and palpable or sonographically detected testis were randomly assigned into two groups: with and without intranasal gonadorelin treatment. Inclusion criteria were met by 36 boys (21 in GNRH and 15 in the control groups). The following orchidopexy was performed before 12 months of age with repeated examination at time of surgery. Penile size and testicular volume (using ultrasound) and basal serum levels of LH, FSH, testosterone, Inhibin B and AMH were recorded at age of 3.0 (mean) months and 11.0 (mean) months (date of surgery). The stimulation hormonal levels were checked during GnRH administration. Results: Between minipuberty (mean 3 months) and time of orchidopexy (mean 11 months of age) the penile size increased significantly and similarly in both groups. There was no significant difference in the change of the volume of descended testis between the groups nor of the volume of undescended testis. In addition, we did not find any significant difference in the change (drop) of hormonal levels of LH, FSH, Testosterone, Inhibin B and AMH (Table 1a) Conclusion: The neoadjuvant gonadorelin stimulation in infants with unilateral undescended testis has not shown any specific effect on the development of penile size, testicular volume and hormonal levels at time of orchidopexy in comparison with boys without stimulation, and in the mid-term, this treatment can be considered safe. Further follow-up is necessary to evaluate the long-term effect of this early treatment.